Convergent construct validity and test-retest reliability of both German versions of the original and the revised Niigata PPPD Questionnaire: NPQ and NPQ-R - Chételat, Sarah; Gerber, Eve-Yaël; El Khadlaoui, Sarah; Behrendt, Frank; Stark, Michaela; Schädler, Stefan; Maywald, Maximilian; Fabritius, Lena; Gerb, Johannes; Grabova, Denis; Trost, Wiebke; Zwergal, Andreas; et al. (Frontiers in Neurology, 2025)
BackgroundPersistent Postural-Perceptual Dizziness (PPPD) is a frequent chronic functional disorder that manifests with dizziness, unsteadiness, or non-spinning vertigo present for at least 3 months. Characteristic provocation factors are moving or complex visual stimuli and exclusion of organic diseases. To assess the severity and impact of PPPD, Japanese researchers developed the Niigata PPPD Questionnaire (NPQ). The study's aim was to evaluate the concurrent construct validity and reliability [including test-retest reliability, internal consistency, standard error of measurement (SEM), and minimal detectable change (MDC)] of the German version of the NPQ (12 items) and its revised version, NPQ-R, which contains 19 items addressing additional symptoms and symptom behavior.MethodsThe Swiss Reha Rheinfelden and the German Center for Vertigo and Balance Disorders included 265 PPPD patients (mean age 50.2 ± 16.8 years, disease duration 46.3 ± 76.6 months). Patients completed the NPQ and the NPQ-R (twice), the DHI and potentially related constructs: anxiety (ABC-Scale, VSS), depression (HADS), and general health (SF-36) once. To assess the questionnaires' reliability and validity, several statistical measures were calculated, including Spearman's rank correlation coefficients, Intraclass Correlation Coefficients (ICC2, 1), Cronbach's alpha, SEM, and MDC.ResultsOn average, patients scored 29.9 ± 13.2 for NPQ and 52.3 ± 19.6 for NPQ-R. Correlations between NPQ/NPQ-R and (1) disease-specific questionnaires were rs= 0.712 and rs= 0.752 (DHI), rs=0.426 and rs= 0.0.462 (VSS-V), rs= -0.500 and rs= -0.545 (ABC-Scale), (2) anxiety-specific subscales rs = 0.394 and rs = 0.430 (VSS-A) and rs= 0.354 and rs= 0.430 (HADS-A), (3) depression-related subscales rs=0.438 and rs= 0.487 (HADS-D), and (4) general health rs ranged between rs= -0.216 and −0.578 (all SF-36 subscales). Internal consistency, test-retest reliability, SEM and MDC calculated for NPQ/NPQ-R were α = 0.88/α = 0.91, ICC=0.83 (CI 0.77 to 0.0.87), SEM 5.55/8.37, and MDC 15/23 points.ConclusionThe German versions of NPQ and NPQ-R are valid and reliable patient-reported outcome measures for assessing PPPD, demonstrating satisfactory psychometric measurement properties including convergent construct validity and reliability parameters: internal consistency, test-retest reliability, SEM, and MDC as an evaluative measure. The NPQ-R, with its additional subscales addressing associated symptoms and symptom behavior, represents both the patient and clinician perspective on PPPD-specific problems. Therefore, we recommend utilizing the NPQ-R for a comprehensive assessment of PPPD.